Design of Self‐Powered Sensors with Excellent Thermal and UV–Light Detections by 0.94(Bi0.5Na0.5)TiO3‐0.06Ba(Zr0.25Ti0.75)O3 Nanoparticles. (10th July 2022) - Zhao, Kun; Zhang, Hui; Meng, Jingke; Chung, Chia‐Chen; Gu, Bing‐Ni; Liu, Ming‐Jin; Zhang, Ding; Zhong, Ming; Liu, Maocheng; Liu, Na; Lin, Chun‐Jung; Meng, Cheng; et al.
Abstract: Ferroelectric materials provide a new pathway to convert thermal energy into electricity based on the pyroelectric effect. How to modulate the pyroelectric property of ferroelectric materials through UV–light is still an urgent problem that needs to be solved. Here, a self‐powered sensor is demonstrated based on 0.94(Bi0.5 Na0.5 )TiO3 ‐0.06Ba(Zr0.25 Ti0.75 )O3 nanoparticles, exhibiting high output electric performance under temperature variation and UV–light illumination conditions. Compared with a purely pyroelectric system, the corresponding current peaks of "UV–light + heating" and "UV–light + cooling" states are 88.6% higher and 37.3% smaller in the coupled system. The fabricated pyroelectric system shows excellent performance with detection sensitivities of 0.9 (heating) and 1.48 nA K −1 (cooling) with 0.7 × 10 −3 and 0.2 × 10 −3 nA lux −1 illuminated by 395 nm UV–light as a temperature sensor. Furthermore, a self‐powered sensor that is suitable for detecting both UV–light and temperature variations by recording the output current signals are demonstrated, which provides a basis for the development of the next generation of UV–light‐modulated ferroelectric devices. Abstract : A self‐powered sensor is demonstrated based on 0.94(Bi0.5 Na0.5 )TiO3 ‐0.06Ba(Zr0.25 Ti0.75 )O3 nanoparticles, exhibiting high output electric performance under temperature variation and UV–light illumination conditions. The fabricated pyroelectric system shows excellent performance with detection sensitivities of 0.9 nA K −1 (heating) and 1.48 nA K −1 (cooling) with 0.7 × 10 –3 and 0.2 × 10 –3 nA lux −1 illuminated by 395 nm UV–light as a temperature sensor. Furthermore, a self‐powered sensor that is suitable for detecting both UV–light and temperature variations by recording the output current signals are demonstrated, which provides a basis for the development of the next generation of UV–light‐modulated ferroelectric devices.